122k views
1 vote
3y-5z=-23
4x+2y+3z=7
-2x-y-z=-3

User Cintra
by
4.9k points

2 Answers

4 votes
Hope it helps you(The pictures are where the answer is)
3y-5z=-23 4x+2y+3z=7 -2x-y-z=-3-example-1
User Jed Fox
by
5.7k points
5 votes

Answer: x = 4, y = -6, z = 1

Explanation:

EQ2: 4x + 2y + 3z = 7 → 1(4x + 2y + 3z = 7) → 4x + 2y + 3z = 7

EQ3: -2x - y - z = -3 → 2(-2x - y - z = -3) → -4x -2y - 2z = -6

z = 1

EQ1: 3y - 5z = -23

3y - 5(1) = -23

3y - 5 = -23

3y = - 18

y = -6

EQ3: -2x - y - z = -3

-2x - (-6) -(1) = -3

-2x + 6 - 1 = -3

-2x + 5 = -3

-2x = -8

x = 4

User Derekcohen
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.